Cyber Risk Management Disclosure: - Sofiani, Mira; Ramadhanty, Diani Putri; Jubaedah, Siti (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to determine the impact of firm size, profitability, and intangible assets on cyber risk management disclosure. Design/methodology/approach: This research is a causality study with quantitative methods and uses secondary data derived from annual reports of telecommunications and financial services sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used purposive sampling and obtained 150 annual reports which were analyzed using multiple linear regression. Findings: The results showed that company size and profitability have a positive and significant influence on Cyber Risk Management Disclosure, but Intangible Assets are not significant. Practical implications: According to the research outcomes, it is suggested for the development of government policies and regulations that encourage companies to increase cyber risk management disclosures in annual reports, as well as companies can understand the factors that influence cyber risk management disclosures so that companies can increase transparency and reduce cyber risk, besides that it can help investors make wiser investment decisions by having an understanding of cyber risk management faced by companies. Originality/value: This research contributes to the development of an accounting conceptual framework on the concept of disclosure, especially voluntary disclosure and practical contributions for governments, companies, and investors. Paper type: Research paper